2021
DOI: 10.1039/d0sm01346c
|View full text |Cite
|
Sign up to set email alerts
|

Evaporation-driven colloidal cluster assembly using droplets on superhydrophobic fractal-like structures

Abstract: Evaporation of suspension droplets on superhydrophobic substrates reveals a dominant shape dependency of the resulting supraparticles on initial particle concentration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 56 publications
(76 reference statements)
1
22
0
Order By: Relevance
“…2 we can see that, during a first stage of the evaporation process, the droplet volume evolves in time just like pure water droplets (solid lines), regardless of their composition (symbols). This is fairly well described by a simple model valid for pure water solutions, and has recently been shown for colloidal solutions [33]. Thus we conclude that the early evaporation process is not affected by the composition of the droplet, no matter the relative humidity, just as suggested by our analytical model described below.…”
Section: Experimental Results With Respiratory-like Dropletssupporting
confidence: 83%
See 2 more Smart Citations
“…2 we can see that, during a first stage of the evaporation process, the droplet volume evolves in time just like pure water droplets (solid lines), regardless of their composition (symbols). This is fairly well described by a simple model valid for pure water solutions, and has recently been shown for colloidal solutions [33]. Thus we conclude that the early evaporation process is not affected by the composition of the droplet, no matter the relative humidity, just as suggested by our analytical model described below.…”
Section: Experimental Results With Respiratory-like Dropletssupporting
confidence: 83%
“…This is a surprising phenomenon since a quick calculation can show that the time scale for the Brownian motion of, for example, a sodium ion is much shorter than the evaporation time scale. However, it can be shown that a salt concentration gradient can form in an evaporating droplet due to the non-linear dynamics of the receding interface [17], and a similar phenomenon has been shown to occur with colloids, yielding core-shell structures [33]. Consequently, it is not surprising that mucin and surfactant accumulate at the interface forming a sort of film, which could wrap (and protect) any other non-volatile content.…”
Section: Droplet Dry-out and Resulting Structurementioning
confidence: 99%
See 1 more Smart Citation
“…In particular, it would be interesting to study the additional role of the ratio of volumes of oil and particles in determining the supraparticle shape, along the lines of Tan et al ., and how this ratio interferes with the effect of colloidal particle size. Furthermore, a question to be addressed is whether our findings can be generalized and applied to the production of supraparticles on other substrates, such as structured superhydrophobic surfaces or oil-coated surfaces, and whether the pinning can be avoided completely or for a major part of the evaporation process on structured surfaces. ,, As the shape of the supraparticle has been leveraged for desirable functionality of the supraparticle in the extensive literature, , it will also be exciting to explore the functionalities of these supraparticles in the future.…”
Section: Resultsmentioning
confidence: 99%
“…In the literature, the evaporation of colloidal suspensions has been extensively studied with the objective of directing the assembly of colloids over a surface. When a drop containing a colloidal suspension is evaporated on a surface, the resulting deposited residue may exhibit typical edge rings. This so-called “coffee ring” effect is due to the pinning of the contact line of the drop with the surface .…”
Section: Introductionmentioning
confidence: 99%